Physiotherapists' attitudes towards and challenges of working in a referral-based practice setting – a systematic scoping review. (2nd November 2021) - Lim, Wil Son; Sharma, Saurab; Devan, Hemakumar
Abstract: Background: The World Confederation for Physical Therapy (WCPT) identifies physiotherapists as autonomous practitioners. However, physiotherapists in many countries do not have this 'right' to practice due to referral-based practice system. It is unknown how it impacts physiotherapists and their ability to deliver person-centred care. Objectives: To synthesise physiotherapists' perspectives of working in countries with limited autonomy in a referral-based physiotherapy setting. Study design: A systematic scoping review. Data sources: Major electronic databases including MEDLINE, AMED, EBM reviews, PsycINFO, Scopus, Web of Science, ProQuest and Google Scholar; and Grey literature including EThOS and Open Grey were searched until June 2019. Study selection: Studies were included if they explored the perspectives of physiotherapists' towards professional autonomy in countries where there is no self-referral or direct access to physiotherapy services. Synthesis methods: Thematic analysis was used to extract common themes. Results: Of the 13 included studies, 9 were qualitative and 4 were quantitative. Four main themes were identified: Physiotherapists reported (1) 'feelings of frustration' and 'low self-esteem', (2) restrictions with critical thinking and clinical reasoning, (3) limited opportunities to provide evidence-based care and (4) difficulty to develop rapport with clients. Conclusions: Physiotherapists working in countries with limited autonomy commonly experience a sense of frustration due to their inability to critically think and provide evidence-based care. Ultimately, these frustrations led to increased occupational stress, reduced job satisfaction and global migration. Although physiotherapists aspire to become autonomous practitioners, the socio-political barriers to achieve legal regulation remain a key challenge to provide person-centred care.